2006
DOI: 10.1590/s1678-77572006000600010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol consumption on periodontal bone support in experimental periodontitis in rats

Abstract: Objective:The aim of this study was to evaluate the effect of the alcohol consumption on the periodontal bone support (PBS) in experimental periodontitis in rats.Materials and Methods:Sixty-three male rats were divided into seven groups: G1 (control); G2 (10% ethanol); G3 (nutritional control of G2); G4 (20% ethanol); G5 (nutritional control of G4); G6 (30% ethanol) and G7 (nutritional control of G6). The groups G3, G5 and G7 received controlled diets with equivalent caloric amounts to those consumed in G2, G4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 28 publications
0
38
1
3
Order By: Relevance
“…26 A recent study observed that, in male rats, periodontitis induction led to greater periodontal bone destruction when associated with alcohol intake at concentrations of 10%, 20% and 30%. 27 Compared to the present study, these results suggest that the effects of alcohol consumption in male rats may be observed in lower concentration of ethanol than in female rats.…”
Section: Discussioncontrasting
confidence: 86%
“…26 A recent study observed that, in male rats, periodontitis induction led to greater periodontal bone destruction when associated with alcohol intake at concentrations of 10%, 20% and 30%. 27 Compared to the present study, these results suggest that the effects of alcohol consumption in male rats may be observed in lower concentration of ethanol than in female rats.…”
Section: Discussioncontrasting
confidence: 86%
“…Research suggests that alcohol consumption is associated with the increase of severity of periodontitis in humans [4][5]19 , periodontal inflammation [14][15] and alveolar bone loss in periodontal disease in rats [11][12][13] . However, others studies on humans have shown no relation between periodontal disease and alcohol intake [9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies on humans have shown no relation between periodontal disease and alcohol consumption [6][7] . The use of rat models has been applied in the evaluation of periodontal pathogenesis 8 and regarding the influence of risk indicator/factors, such as estrogen deficiency [9][10] , alcohol consumption [11][12][13][14][15][16] , nicotine 17 and simultaneous nicotine and alcohol use 18 on disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…[7,19], and histologic [12] or histometric [9] analyses applied to jaws. However, the morphometric methods adopted to assess alveolar bone level are not capable of detecting intra-osseous defects.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy drinking episodes are associated with detrimental consequences, even when the mean alcohol consumption level is relatively low [1]. Some studies [9,10,18,19,[21][22][23][24] showed that alcohol intake itself might not be capable of causing bone loss in rats' periodontium. On the other hand, other studies [25,26] recorded that chronic alcohol drinking itself may cause bone loss in rats.…”
Section: Discussionmentioning
confidence: 99%